(untitled) (Journal of Informatics Education and Research, 2024)
The use of AI in HRM is changing the ways firms approach the management of talent and the overall organizational development. This study focuses on the present state of affairs and prospects of applying AI in the field of HRM, analysing how AI solutions are applied in the practice to improve several HR activities, including recruitment, performance appraisal, engagement, and workforce planning and analytics. AI integrated recruitment processes, for instance, are redesigning the old conventional techniques by enabling automated screening of candidates, intelligent posting of jobs, and AI based predictions on suitability of candidates. This not only makes work faster but also eliminates the problem of bias Hence, making the hiring process fair. Now in the performance management system, AI is also helping in providing feedback and development plans on ongoing basis leading to a more flexible work environment. Several employee engagement strategies are being boosted by techniques that are anchored on AI and these include; In addition, workforce analytics based on AI allow offering detailed information on people’s behavior thus making proper decisions and successful people management. Still, it is imperative to understand the underlying challenges of applying AI in the practices of the HR department. Thus, issues related to ethic, such as data privacy issue and the so called ‘feedback loop’ that may magnify bias are major problems that should be considered. It also incurs the need to train the existing human resource professionals to work with AI as they work towards achieving their company’s goals. The research focuses on the creation of guidelines for ethical integration of AI, including transparency, accountability, and the deviation of stakeholders’ AI decision-making processes.